Iron-induced gastric ulceration with radiological and endoscopic appearance of carcinoma. (6th October 2015) - Smith, Iain M; Bryson, Gareth; Glen, Paul
Abstract : Erosive injury of the upper gastrointestinal tract resulting from therapeutic oral iron supplements is an uncommon phenomenon. We present a case of a large gastric ulcer with clinical, endoscopic and radiological features suggestive of malignancy, which resolved completely on cessation of iron therapy.